2005
DOI: 10.1002/qsar.200420059
|View full text |Cite
|
Sign up to set email alerts
|

Application of Data Mining and Evolutionary Optimization in Catalyst Discovery and High‐Throughput Experimentation – Techniques, Strategies, and Software

Abstract: Data-mining and evolutionary optimization techniques are powerful tools to improve the efficiency of high-throughput experimentation (HTE) to discover new materials, drugs, or catalysts. The parameter space of screening experiments is usually high-dimensional and the parameters are possibly discrete. The response surface of the screened systems can be very rugged, characterized by smooth planes as well as steep and narrow ascents of abundant sub-optima. These conditions make exclusive use of classical statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…This review also provides a large bibliography for data mining in HTE, including textbooks that provide theoretical background. Ohrenberg et al [103] have reported how data mining and evolutionary optimization can be used to increase the efficiency of material searches in high-dimensional parameter spaces. The authors used different data-mining techniques, such as clustering, correlation analysis, and decision trees, in combination with evolutionary strategies for materials optimization.…”
Section: Reviewsmentioning
confidence: 99%
“…This review also provides a large bibliography for data mining in HTE, including textbooks that provide theoretical background. Ohrenberg et al [103] have reported how data mining and evolutionary optimization can be used to increase the efficiency of material searches in high-dimensional parameter spaces. The authors used different data-mining techniques, such as clustering, correlation analysis, and decision trees, in combination with evolutionary strategies for materials optimization.…”
Section: Reviewsmentioning
confidence: 99%
“…Fig. 9 represents a screenshot of an OptiCat workflow that utilizes a Genetic Algorithm (GA) [18][19][20][21]. The definition of the parameter space, like variable names and limits, and the configuration settings are set from the main OptiCat user interface.…”
Section: Integration Of Opticat Applicationmentioning
confidence: 99%
“…This review also provides a large bibliography for data mining in HTE, including textbooks that provide theoretical background. Ohrenberg et al 103. have reported how data mining and evolutionary optimization can be used to increase the efficiency of material searches in high‐dimensional parameter spaces.…”
Section: Computational Toolsmentioning
confidence: 99%